Methods of Re-Education of Specific Learning Disorders - Weiss, Ervin; Akimjaková, Beáta; Paľa, Gabriel; Biryukova, Yulia Nickolaeva (Journal of Education Culture and Society, 2023)
Aim. In a qualitative empirical exploration, the authors use case study research to identify opportunities for re-education of specific learning disabilities in two cases. They identify and analyse the methods and organisation of teaching and the intervention plan for change. They evaluate the effectiveness of the intervention procedures and highlight specific practical experiences of educators in working with pupils.Methods. The study analyses and interprets the risk of specific learning disabilities, identifies specific learning disabilities. In an empirical qualitative investigation, the authors use case studies and case studies that highlight two types of specific learning disabilities.Results. The studies confirm that specific developmental learning disabilities affect the lives not only of the pupils themselves, the parents, but not least the educators in the teaching process. The authors analyse and identify specific re-education methods in the implementation of the teaching process, pointing out the difficulty of solving the problem and unlearning special educators.Conclusion. The authors point out the need for selection of different methods of re-education of learning disorders on the basis of the individuality of the pupil, but also on the basis of different forms of solving problem areas in terms of recommendations of the special educator and the actual implementation of the teaching process by the educator.